Preparation method of fast-charging artificial graphite negative electrode material

By regulating the cross-linking structure of asphalt and resin and forming a pore structure on the surface of graphite materials, the problem of limited fast charging applications of graphite materials in lithium-ion batteries is solved, and rapid diffusion and stable coating of lithium ions are achieved, significantly improving Improves the fast charging performance of lithium-ion batteries.

CN119320131APending Publication Date: 2025-01-17XIANTAO HAIRONG NEW ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410218490.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the prior art, the application of fast charging of graphite materials in lithium-ion batteries is limited by the problem of small layered structure and solid phase diffusion coefficient of the material, and the performance improvement of commonly used carbon coating methods is limited, making it difficult to meet higher need.

Method used

By regulating the composite structure formed by cross-linking of asphalt and resin, and using steps such as mechanical mixing, sintering, graphitization and coating agent preparation, fast-charging artificial graphite anode materials are prepared. This method forms a pore structure on the surface of the graphite material, increases the diffusion channel of lithium ions, increases the solid phase diffusion rate, and improves the material performance through a new coating agent.

Benefits of technology

It achieves rapid diffusion and stable coating of lithium ions, reduces the risk of polarization and lithium precipitation of the battery, and significantly improves the fast charging performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of negative electrode materials, in particular to a preparation method of a fast-charging artificial graphite negative electrode material, which comprises the following steps: S1, coarsely breaking, drying and crushing one or more of needle coke green coke, petroleum coke green coke, needle coke calcined coke and petroleum coke calcined coke to obtain a precursor A; s2, mixing inorganic alkali and / or organic alkali to obtain a pore-forming agent B; s3, mechanically mixing the precursor A obtained in the step S1 and the pore-forming agent B obtained in the step S2 according to the mass ratio of 100: (5-20) to obtain a precursor C; s4, sintering the precursor C to obtain a modified porous precursor D; s5, performing high-temperature graphitization treatment on the porous precursor D to obtain porous artificial graphite E; s6, asphalt and resin are mixed according to the ratio, and then a coating agent F is obtained; and S7, mixing the porous artificial graphite E with a coating agent F, and granulating to obtain the fast-filling artificial graphite G. The material is endowed with excellent and stable performance by regulating and controlling a composite structure formed by mutual crosslinking of asphalt and resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a method for preparing a fast-charging artificial graphite negative electrode material. Background Art

[0002] Due to the layered structure of graphite materials, lithium ions must be embedded from the end faces of the material and then diffuse into the interior of the particles, resulting in a longer transmission path and a larger irreversible capacity. The slower lithium insertion process hinders the fast charging application of lithium-ion batteries. In liquid electrolyte systems, the solid-phase diffusion coefficient of lithium in graphite is relatively small (usually only about 10-10cm2.s-1), which limits its application in fast charging.

[0003] Carbon coating is the most common material modification method. The material is carbon-coated. The commonly used carbon coating in the industrial field is single solid asphalt coating. If only asphalt coating is used or the amount is too large, the material is easy to agglomerate. If only resin coating is used, the coating layer is difficult to stabilize due to poor compatibility with graphite, and the performance improvement is limited, and it is difficult to meet higher demands; such as CN202110968525.4 A fast-charging, high-initial-effect hard carbon / artificial graphite negative electrode material and its preparation method; CN202310123678.8 A fast-charging artificial graphite negative electrode material and its preparation method and lithium-ion battery; CN202011453338.4 A high-density fast-charging artificial graphite material and its preparation method.

[0004] Therefore, by regulating the composite structure formed by the cross-linking of asphalt and resin, the material is endowed with excellent and stable properties, and a method for preparing a fast-charging artificial graphite negative electrode material is proposed. Summary of the invention

[0005] In view of the above situation, in order to overcome the defects in the prior art that the commonly used carbon coating in the industrial field is a single solid asphalt coating, with limited performance improvement and difficulty in meeting higher demands, the present invention provides a method for preparing a fast-charging artificial graphite negative electrode material.

[0006] The technical solution adopted by the present invention is as follows: A method for preparing a fast-charging artificial graphite negative electrode material comprises the following steps:

[0007] S1. Raw material pretreatment: the raw material is one or more of needle coke green coke, petroleum coke green coke, needle coke calcined coke, and petroleum coke calcined coke, which is coarsely broken and dried at a drying temperature of 90 to 160°C for 60 to 240 minutes to a moisture content of ≤3%, and then crushed to D50 = 5 to 20 um to obtain a precursor A;

[0008] S2. Pore forming agent pretreatment: mixing an inorganic base and / or an organic base to obtain a pore forming agent B, wherein the pore forming agent B has a pH of 7 to 11 and a volume concentration of 30% to 50%;

[0009] S3. The precursor A obtained in S1 and the pore-forming agent B obtained in S2 are mechanically mixed in a mass ratio of 100:5-20, and the pore-forming agent B and the precursor A are subjected to three-dimensional circulation, high-speed high-frequency compression and shear force during mixing to achieve good infiltration of the particle surface, and then the precursor C is obtained, wherein the mixing time is 60-150 minutes;

[0010] S4. Sintering the precursor C, wherein the sintering equipment parameter settings include but are not limited to a temperature of 600 to 800° C. and a time of 400 to 600 min to obtain a modified porous precursor D;

[0011] S5. The porous precursor D is subjected to high temperature graphitization to obtain porous artificial graphite E;

[0012] S6. Coating agent preparation: The asphalt having a softening point of 110 to 180°C and the resin having a softening point of 50 to 180°C are mixed in a mass ratio of 5:1 to 5 to obtain a coating agent F, and the mixing time is 30 to 150 min;

[0013] S7. The porous artificial graphite E and the coating agent F are mechanically mixed in a mass ratio of 100:1 to 30 and then granulated in a reactor at a granulation temperature of 400 to 700° C. for 360 to 600 min to obtain fast-charging artificial graphite G.

[0014] Furthermore, the inorganic base in S2 includes but is not limited to sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, etc.

[0015] Furthermore, the organic base in S2 includes but is not limited to methylamine, urea, ethylamine, ethanolamine, ethylenediamine, chlorophenol, etc.

[0016] Furthermore, the asphalt described in S6 includes but is not limited to one or more of coal-modified asphalt, petroleum asphalt, modified asphalt, and mesophase asphalt.

[0017] Furthermore, the resin in S6 includes but is not limited to one or more of furan resin, phenolic resin, epoxy resin, and polyoxymethylene methyl acrylate resin.

[0018] The beneficial effects achieved by the present invention using the above structure are as follows:

[0019] 1. Etch the pores on the surface of graphite material to form holes in the graphite material, which increases the diffusion channel of lithium. Lithium can be embedded from the base surface, shortening the transmission distance, increasing the diffusion speed, and improving the solid phase diffusion of lithium in graphite, effectively reducing the polarization and lithium precipitation risks of the battery, and improving the fast charging performance of lithium-ion batteries;

[0020] 2. The conventional solid asphalt solid phase coating in the industry has limited improvement on the fast charging performance of materials. The use of new coating agents can greatly improve the performance of materials;

[0021] 3. The composite structure formed by regulating the cross-linking of asphalt and resin gives the material excellent and stable properties. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] Embodiment 1, a method for preparing a fast-charging artificial graphite negative electrode material, comprising the following steps:

[0024] S1. Raw material pretreatment: The raw materials are needle coke and petroleum coke, which are coarsely broken and dried at a drying temperature of 120°C for 150 min to a moisture content of ≤3%, and then crushed to D50 = 8 to 12 um to obtain a precursor A;

[0025] S2. Pore forming agent pretreatment: mixing an inorganic base and / or an organic base to obtain a pore forming agent B, wherein the pore forming agent B has a pH of 8 to 9 and a volume concentration of 35% to 45%;

[0026] The inorganic base includes sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate;

[0027] The organic base includes methylamine, urea (urea), ethylamine, ethanolamine, ethylenediamine, and chlorophenol;

[0028] S3. The precursor A obtained in S1 and the pore-forming agent B obtained in S2 are mechanically mixed in a mass ratio of 100:13, and the pore-forming agent B and the precursor A are subjected to three-dimensional circulation, high-speed high-frequency compression and shear force during mixing to achieve good infiltration of the particle surface, and then the precursor C is obtained, wherein the mixing time is 105 min;

[0029] S4. Sintering the precursor C, wherein the sintering equipment parameter settings include but are not limited to a temperature of 700° C. and a time of 500 min to obtain a modified porous precursor D;

[0030] S5. The porous precursor D is subjected to high temperature graphitization to obtain porous artificial graphite E;

[0031] S6. Preparation of coating agent: The asphalt with a softening point of 145°C and the resin with a softening point of 115°C were mixed in a mass ratio of 5:3 to obtain a coating agent F, and the mixing time was 90 min;

[0032] The asphalt includes but is not limited to one or more of coal-modified asphalt, petroleum asphalt, modified asphalt, and mesophase asphalt;

[0033] The resin includes but is not limited to one or more of furan resin, phenolic resin, epoxy resin, and polyoxymethylene methyl acrylate resin;

[0034] S7. The porous artificial graphite E and the coating agent F are mechanically mixed in a mass ratio of 100:15 and then granulated in a reactor. The reactor is a vertical reactor, a horizontal reactor or a continuous reactor, etc. The granulation temperature is 550° C. and the time is 480 min to obtain fast-charging artificial graphite G.

[0035] Embodiment 2, a method for preparing a fast-charging artificial graphite negative electrode material, comprising the following steps:

[0036] S1. Raw material pretreatment: needle coke raw material is selected, and it is coarsely broken and dried at a drying temperature of 90°C for 60 minutes, dried to a moisture content of ≤3%, and then crushed to D50 = 8 ~ 12um to obtain precursor A;

[0037] S2. Pore forming agent pretreatment: mixing an inorganic base and / or an organic base to obtain a pore forming agent B, wherein the pore forming agent B has a pH of 8 to 9 and a volume concentration of 35% to 45%;

[0038] The inorganic base includes but is not limited to sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate;

[0039] The organic base includes but is not limited to methylamine, urea (urea), ethylamine, ethanolamine, ethylenediamine, and chlorophenol;

[0040] S3. The precursor A obtained in S1 and the pore-forming agent B obtained in S2 are mechanically mixed in a mass ratio of 100:5, and the pore-forming agent B and the precursor A are subjected to three-dimensional circulation, high-speed high-frequency compression and shear force during mixing to achieve good infiltration of the particle surface, and then the precursor C is obtained, wherein the mixing time is 60 minutes;

[0041] S4. Sintering the precursor C, wherein the sintering equipment parameter settings include but are not limited to a temperature of 600° C. and a time of 400 min to obtain a modified porous precursor D;

[0042] S5. The porous precursor D is subjected to high temperature graphitization to obtain porous artificial graphite E;

[0043] S6. Preparation of coating agent: The asphalt with a softening point of 110°C and the resin with a softening point of 50°C were mixed in a mass ratio of 5:1 to obtain a coating agent F, and the mixing time was 30 min;

[0044] The asphalt includes but is not limited to one or more of coal-modified asphalt, petroleum asphalt, modified asphalt, and mesophase asphalt;

[0045] The resin includes but is not limited to one or more of furan resin, phenolic resin, epoxy resin, and polyoxymethylene methyl acrylate resin;

[0046] S7. The porous artificial graphite E and the coating agent F are mechanically mixed in a mass ratio of 100:1 and granulated in a reactor, wherein the reactor is a vertical reactor, a horizontal reactor or a continuous reactor, etc. The granulation temperature is 400° C. and the time is 360 minutes to obtain fast-charging artificial graphite G.

[0047] Embodiment 3, a method for preparing a fast-charging artificial graphite negative electrode material, comprising the following steps:

[0048] S1. Raw material pretreatment: The raw materials are needle coke green coke, petroleum coke green coke, needle coke calcined coke, and petroleum coke calcined coke. After rough crushing and drying, the drying temperature is 160°C, the time is 240min, and the moisture content is ≤3%, and then crushed to D50 = 8 ~ 12um to obtain precursor A;

[0049] S2. Pore forming agent pretreatment: mixing an inorganic base and / or an organic base to obtain a pore forming agent B, wherein the pore forming agent B has a pH of 8 to 9 and a volume concentration of 35% to 45%;

[0050] The inorganic base includes but is not limited to sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate;

[0051] The organic base includes but is not limited to methylamine, urea (urea), ethylamine, ethanolamine, ethylenediamine, and chlorophenol;

[0052] S3. The precursor A obtained in S1 and the pore-forming agent B obtained in S2 are mechanically mixed in a mass ratio of 100:20, and the pore-forming agent B and the precursor A are subjected to three-dimensional circulation, high-speed high-frequency compression and shear force during mixing to achieve good infiltration of the particle surface, and then the precursor C is obtained, wherein the mixing time is 150 min;

[0053] S4. Sintering the precursor C, wherein the sintering equipment parameter settings include but are not limited to a temperature of 800° C. and a time of 600 min to obtain a modified porous precursor D;

[0054] S5. The porous precursor D is subjected to high temperature graphitization to obtain porous artificial graphite E;

[0055] S6. Coating agent preparation: The asphalt having a softening point of 180°C and the resin having a softening point of 180°C were mixed in a mass ratio of 5:5 to obtain a coating agent F, and the mixing time was 150 minutes;

[0056] The asphalt includes but is not limited to one or more of coal-modified asphalt, petroleum asphalt, modified asphalt, and mesophase asphalt;

[0057] The resin includes but is not limited to one or more of furan resin, phenolic resin, epoxy resin, and polyoxymethylene methyl acrylate resin;

[0058] S7. The porous artificial graphite E and the coating agent F are mechanically mixed in a mass ratio of 100:30 and then granulated in a reactor. The reactor is a vertical reactor, a horizontal reactor or a continuous reactor, etc. The granulation temperature is 700° C. and the time is 600 min to obtain fast-charging artificial graphite G.

[0059] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a fast-charging artificial graphite negative electrode material, characterized in that: The steps include: S1. Raw material pretreatment: the raw material is one or more of needle coke green coke, petroleum coke green coke, needle coke calcined coke, and petroleum coke calcined coke. The raw material is coarsely broken and dried at a drying temperature of 90 to 160°C for 60 to 240 minutes until the moisture content is ≤3%. The raw material is then crushed to D50 = 5 to 20 um to obtain a precursor A. S2. Pore forming agent pretreatment: mixing an inorganic base and / or an organic base to obtain a pore forming agent B, wherein the pore forming agent B has a pH of 7 to 11 and a volume concentration of 30% to 50%; S3. The precursor A obtained in S1 and the pore-forming agent B obtained in S2 are mechanically mixed in a mass ratio of 100:5-20, and the pore-forming agent B and the precursor A are subjected to three-dimensional circulation, high-speed high-frequency compression and shear force during mixing to achieve good infiltration of the particle surface, and then the precursor C is obtained, wherein the mixing time is 60-150 minutes; S4. Sintering the precursor C, wherein the sintering equipment parameter settings include but are not limited to a temperature of 600 to 800° C. and a time of 400 to 600 min to obtain a modified porous precursor D; S5. The porous precursor D is subjected to high temperature graphitization to obtain porous artificial graphite E; S6. Coating agent preparation: The asphalt having a softening point of 110 to 180°C and the resin having a softening point of 50 to 180°C are mixed in a mass ratio of 5:1 to 5 to obtain a coating agent F, and the mixing time is 30 to 150 min; S7. The porous artificial graphite E and the coating agent F are mechanically mixed in a mass ratio of 100:1 to 30 and then granulated in a reactor at a granulation temperature of 400 to 700° C. for 360 to 600 min to obtain fast-charging artificial graphite G.

2. The method for preparing a fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The raw material in S1 is preferably needle coke.

3. The method for preparing a fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The precursor A in S1 preferably has D50=8-12 um.

4. The method for preparing a fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The pH of the pore former B in S2 is preferably 8-9, and the volume concentration is preferably 35%-45%.

5. The method for preparing a fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The inorganic base in S2 includes but is not limited to sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate.

6. The method for preparing a fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The organic base in S2 includes, but is not limited to, methylamine, urea, ethylamine, ethanolamine, ethylenediamine, and chlorophenol.

7. The method for preparing a fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The asphalt described in S6 includes, but is not limited to, one or more of coal-modified asphalt, petroleum asphalt, modified asphalt, and mesophase asphalt.

8. The method for preparing a fast-charging artificial graphite negative electrode material according to claim 1, characterized in that: The resin in S6 includes, but is not limited to, one or more of furan resin, phenolic resin, epoxy resin, and polyoxymethylene methyl acrylate resin.

Citation Information

Patent Citations

  • High-compaction quick-charging artificial graphite material and preparation method thereof

    CN112582592A

  • A fast-charging, high-efficiency hard carbon / artificial graphite anode material and its preparation method

    CN113697804B

  • Fast-charging artificial graphite negative electrode material, preparation method thereof and lithium ion battery

    CN116053442A